PS-BPC02-8: EARLY VASCULAR AGING IN HYPERTENSION IS A PREDICTOR OF INCIDENT DIABETES. (January 2023) - Terentes-Printzios, Dimitrios; Christopoulou, Georgia; Korogiannis, Lampros; Ioakeimidis, Nikolaos; Aznaouridis, Konstantinos; Dima, Ioanna; Gardikioti, Vasiliki; Oikonomou, Dimitrios; Gkini, Konstantia P.; Solomou, Eirini; Tsioufis, Konstantinos; Vlachopoulos, Charalambos
Abstract : Objective: Diabetes is associated with vascular aging and arteriosclerosis. Arterial stiffness can be used to assess vascular aging and is an independent predictor of cardiovascular events and mortality. However, the role of arterial stiffness in the incidence of diabetes and especially in patients under treatment with statins has not been investigated. We sought to investigate the role of carotid-femoral pulse wave velocity (PWV) in the prediction of incident diabetes in hypertensives and hypertensives under treatment with statins. Design and method: 376 never treated hypertensives (mean age 53 ± 13 years, 175 females) without a known history of diabetes or cardiovascular disease at baseline, were included in the study. Markers of target organ damage [carotid femoral PWV, aortic augmentation index (AIx), and estimated glomerular filtration rate (eGFR)] were evaluated at baseline in all patients. eGFR was estimated using the Cockcroft Gault formula. Hemoglobin A1c (HbA1c) and blood glucose were measured in venous blood samples. Patients were followed up prospectively for the incidence of diabetes as defined by the American Diabetes Association criteria. One hundred and thirty-nine patients received statins during follow up. Results: During a median of 13.5 years of follow up, 46 patients (12.2%) patients were diagnosed with diabetes. In multivariable logistic regression analysis, only higher PWV (Odds Ratio [OR] = 1.271, 95% Confidence intervals [CI]: 1.002 to 1.612, P = 0.048) was associated with a higher risk of incident diabetes, which was independent of age, sex, pulse pressure, HbA1c, fasting blood glucose and eGFR (Figure). In further analysis, receiver operating characteristic (ROC) curves were generated to evaluate the ability of PWV to discriminate subjects with diabetes. The area under the curve (AUC) and 95% CIs of the ROC curve was AUC = 0.66 (95% CI: 0.58 to 0.74, P = 0.001) for PWV. In the subgroup of patients under treatment with statins, higher PWV (OR = 1.51, 95% CI: 1.09 to 2.11, P = 0.014) was associated with higher risk of incident diabetes, which was independent of the abovementioned confounders. AIx was not associated with the incidence of diabetes. Conclusions: Higher arterial stiffness, a marker of early vascular aging, is associated with the incidence of diabetes and also can identify subjects under treatment with statins that are more likely to present with diabetes in the future.